Effect of Deposit Interest Regional Development Bank, Deposit Interest Rate Government Bank, Inflation, GDP and Money Supply Against Exchange Rate US Dollar - Elsyan Rienette Marlissa (Journal of Economics and Behavioral Studies, 2016)
The purpose of this study is to analyze the effect of Deposit Interest Rate Regional Development Bank, Bank Deposit Interest Rate Government, Inflation, Economic Growth (Real GDP), and the money supply of the rupiah per US dollar. The study uses panel data regression analysis with the model Random Effects Model (REM) method and Pooled EGLS (cross section random effects). The results show that factors of interest rate Regional Development Bank, the interest rate on deposits Bank government, the level of inflation, economic growth, money supply have the simultaneous and significant impact on the rupiah per US dollar. While the partial test results show that the interest rate on deposits BPD and the amount of money circulating have a significant negative effect on the rupiah per US dollar. While variable economic growth (GDP) has insignificant negative impact on the rupiah per US dollar.